Erythrocyte CD55 mediates the internalization of Plasmodium falciparum parasites - Shakya, Bikash; Patel, Saurabh D; Tani, Yoshihiko; Egan, Elizabeth S (eLife, 2021)
Invasion of human erythrocytes by the malaria parasite Plasmodium falciparum is a multi-step process. Previously, a forward genetic screen for P. falciparum host factors identified erythrocyte CD55 as essential for invasion, but its specific role and how it interfaces with the other factors that mediate this complex process are unknown. Using CRISPR-Cas9 editing, antibody-based inhibition, and live cell imaging, here we show that CD55 is specifically required for parasite internalization. Pre-invasion kinetics, erythrocyte deformability, and echinocytosis were not influenced by CD55, but entry was inhibited when CD55 was blocked or absent. Visualization of parasites attached to CD55-null erythrocytes points to a role for CD55 in stability and/or progression of the moving junction. Our findings demonstrate that CD55 acts after discharge of the parasite’s rhoptry organelles, and plays a unique role relative to all other invasion receptors. As the requirement for CD55 is strain-transcendent, these results suggest that CD55 or its interacting partners may hold potential as therapeutic targets for malaria.
Keywords: erythrocytes; malaria; invasion